School of foreign languages «language mosaic» in the innovative structure of the Mordovian State Pedagogical Institute - Andrey A. Vetoshkin; Alexandra V. Nuzhdina; Svetlana I. Piskunova (Высшее образование в России)
The article analyzes the experience in the development of innovative infrastructure of theuniversity. In particular, the activity of the School of Foreign Languages «Language Mosaic» is described. The school aims to introduce the process-oriented approach into foreign language teaching. The authors discuss the basic teaching methods of applied at school.